SAT0492 RAPID IMPROVEMENT AND ACHIEVEMENT OF INACTIVE DISEASE IN CHILDREN WITH SYSTEMIC JUVENILE IDIOPATHIC ARTHRITIS UNDER 4 YEARS OF AGE DEPENDING ON DISEASE DURATION ON TOCILIZUMAB TREATMENT. (2nd June 2020) - Krekhova, E.; Alexeeva, E.; Dvoryakovskaya, T.; Isaeva, K.; Chomakhidze, A.; Chistyakova, E.; Lomakina, O.; Denisova, R.; Mamutova, A.; Fetisova, A.; Gautier, M.; Vankova, D.; et al.
Abstract : Background: Early-onset form of systemic juvenile idiopathic arthritis (sJIA) often presents severe disease course. Choosing the optimal therapy option as first-line treatment is necessary for rapid improvement of patients' quality of live and prevention of further radiologic progression. Objectives: To evaluate the long-term effectiveness and safety of tociliizumab (TOC) in sJIA patients depending on the duration of the disease treated in the National Medical Research Center of Children`s health, Moscow, Russia. Methods: The study was conducted as a subanalysis of the prospective cohort study to evaluate the efficacy of biologics in children with sJIA. Analysis included sJIA patients younger than 4 years of age at the moment of TOC initiation. Patients were divided into 2 groups: with disease duration shorter than 6 month (ShorterDD group, n=35) and more than 6 month (LongerDD group, n= 19). Treatment efficacy was evaluated according to the dynamics of clinical and laboratory signs using the ACRPedi criteria. The Wallace criteria were used to evaluate whether or not remission had been achieved. Treatment safety was evaluated according to the data presented in the Adverse Event Reports. Results: TOC was first biologics in 34/35 (97.1%) patients in ShorterDD group and 18/19 (94.7%) patients in LongerDD group. Groups were comparable in terms of disease activity at TOC initiation with 100% of patients presented active systemic features. 31/35 (88.6%) patients in ShorterDD group and 17/19 (89.5%) patients in LongerDD group have median 3 (IQR 1: 6) and 5 (IQR 3: 7.5) active joints, respectively (p=0.119). JADAS-71 level was 17.14 ± 6.25 ShorterDD group and 17.36 ± 5.45 in LongerDD group (p=0.895). TOC showed high efficacy after first months of treatment with only 6/35 (17.1%) patients in ShorterDD group and 7/19 (36.8%) in LongerDD group remained with active systemic features (p=0.181). JADAS-71 level decreased to 0 points 26/35 patients (74.3%) in ShorterDD group and in 11/19 patients (57.9%) LongerDD group (p=0.237). After 3 month of treatment, WID was achieved by 27/35 patients (77.1%) in ShorterDD group and by 9/19 patients (47.4%) LongerDD group (p=0.038). ACR Pedi 50/70/90 was achieved by 88.6%/85.7%/80% of patients in ShorterDD group and by 84.2%/73.7%/68.4% of patients in LongerDD group after 1 months of treatment and in 77.1%/74.3%/74.3% and 84.2%/78.9%/68.4%, respectively, after 3 months of treatment. Conclusion: Initiation of tocilizumab treatment in sJIA patients under 4 years of age is highly effective. However, early treatment within first 6 month after disease onset had advantages in speed of reaching an inactive disease as soon as after 3 months of therapy. Disclosure of Interests: Elizaveta Krekhova: None declared, Ekaterina Alexeeva Grant/research support from: Roche, Pfizer, Centocor, Novartis, Speakers bureau: Roche, Novartis, Pfizer., Tatyana Dvoryakovskaya: None declared, Ksenia Isaeva: None declared, Aleksandra Chomakhidze: None declared, Evgeniya Chistyakova: None declared, Olga Lomakina: None declared, Rina Denisova: None declared, Anna Mamutova: None declared, Anna Fetisova: None declared, Marina Gautier: None declared, Dariya Vankova: None declared, Meyri Shingarova: None declared, Alina Alshevskaya: None declared, Andrey Moskalev: None declared, Ivan Kriulin: None declared